The Impact of Teacher Talk Towards Students’ Language Attitude in Learning English Speaking Skill - Mangngemba, Sintike; Tandikombong, Matius; Panggua, Selvi (Indonesian TESOL Journal, 2024)
Students’ language attitude in learning English speaking Skill. The researcher conducted the research used quantitative method. The convenience sampling was used to obtain data from 19 7th semester students of English Education study program who had participated all the speaking class. The data were obtained by questionnare technique. Data were analyzed using the T test, correlation coefficient (Pearson product moment), coefficient of determination and linear regression. The results of hypothesis testing using t test analysis, the t-count value is 5.053 and the t-table is 2.120, meaning that the t-count value is greater than the t table, namely 5.053 > 2.120. with a significance level of 0.00 < 0,05. It means that the Null Hypothesis (H0) is rejected and the Alternative Hypothesis (Ha) is accepted. The conclusion is teacher talk has a positive impact towards students’ language attitude in learning english speaking skill. These results show that teacher talk is an important factor in shaping students' language attitudes, so the communication approach used by lecturers in learning English speaking needs to be designed effectively to achieve better results. Keywords: Impact, Teacher Talk, Language Attitude , English Speaking Skill.